1991
DOI: 10.1161/01.hyp.17.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Relation of electrolytes to blood pressure in men. The Yi people study.

Abstract: The relations of sodium, potassium, calcium, and magnesium to blood pressure were investigated in four groups of men (119 high-mountain Yi farmers, 114 mountainside Yi farmers, 89 Yi migrants, and 97 Han people) with a wide range of electrolyte intake in Puge County, Sichuan Province, People's Republic of China. Electrolytes were measured in diet, serum, and urine. Sodium excretion was 73.9 mmol/24 hr in high-mountain Yi farmers, 117.9 mmol/24 hr in mountainside Yi farmers, 159.4 mmol/24 hr in Yi migrants, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Serum potassium was inversely related to both DBP and SBP in the cohort without hypertension and CHD. A negative association between serum (or plasma) potassium and both DBP and SBP 40 or with DBP only 31 - 41 has been previously observed. There is a well-documented relation between average alcohol intake and elevated BP 42, 43 a n ( j t m s association was confirmed in the CHS among the entire cohort.…”
mentioning
confidence: 63%
“…Serum potassium was inversely related to both DBP and SBP in the cohort without hypertension and CHD. A negative association between serum (or plasma) potassium and both DBP and SBP 40 or with DBP only 31 - 41 has been previously observed. There is a well-documented relation between average alcohol intake and elevated BP 42, 43 a n ( j t m s association was confirmed in the CHS among the entire cohort.…”
mentioning
confidence: 63%
“…5 A positive relation between dietary sodium and BP has been shown from observational studies in humans. The Yi People Study 6 in China compared Yi farmers in remote areas with a group of Yi farmers who had migrated to an urban area and a group of Han residents of the same urban area. BP rose very little with age in the Yi farmers but increased with age in Yi migrants and Han residents.…”
Section: Overview Of Relation Between Sodium and Blood Pressurementioning
confidence: 99%
“…Other factors, such as body mass index (BMI), were also involved. 6 Several large, long-term, randomized clinical trials have shown that a moderate reduction in sodium intake reduces BP levels. The Trials of Hypertension Prevention (TOHP), Phase II, 7 evaluated the benefits of weight reduction and sodium reduction, alone and in combination, for individuals who were slightly to moderately overweight and had high normal BPs.…”
Section: Overview Of Relation Between Sodium and Blood Pressurementioning
confidence: 99%
“…3,4 However, the results of the different studies were inconsistent. [5][6][7][8][9][10][11][12][13][14][15][16] Some methodological problems were considered to be responsible for this heterogeneity. For example, differences in the method of sampling, dietary data collection and assessing calcium intake are possible causes.…”
Section: Introductionmentioning
confidence: 99%